2012
DOI: 10.1111/j.1365-2621.2012.03093.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the protein fractions extracted from the muscle tissue of Pinctada martensii and their hydrolysis by pancreatin

Abstract: Pinctada martensii muscle proteins were separated into water-soluble, salt-soluble and insoluble protein fractions. The salt-soluble protein fraction was the most abundant, comprising approximately 66.3% of the protein, followed by the water-soluble and insoluble protein fractions in decreasing order. sodium dodecyl sulphate polyacrylamide gel electrophoresis profiles showed that 35-and 97-kDa peptides represented the highest proportions of the water-soluble and salt-soluble protein fractions, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Similar results in the muscle tissue of Pinctada martensii were found in a previous study performed by Zheng et al . (2012). A previous study reported the differential expression of proteins of muscle tissue between normal and severe wooden breast meat (Kuttappan et al ., 2017a), but no significant changes were found in the ratios of water‐soluble protein and salt‐soluble protein contents in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results in the muscle tissue of Pinctada martensii were found in a previous study performed by Zheng et al . (2012). A previous study reported the differential expression of proteins of muscle tissue between normal and severe wooden breast meat (Kuttappan et al ., 2017a), but no significant changes were found in the ratios of water‐soluble protein and salt‐soluble protein contents in this study.…”
Section: Resultsmentioning
confidence: 99%
“…A full amino acid profile analysis was conducted according to the method of Zheng et al . (2012). Tryptophan content was determined using 5 M NaOH and 0.3 ml of triglyceride at 110 °C for 24 h. To determine the content in other amino acids, the samples were hydrolysed with 6 m HCl at 110 °C for 24 h. The amino acids of hydrolysed samples were quantified using a high‐speed amino acid analyser (L‐8500A, Hitachi Co., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…[1] At present, only a small part of the meat is marketed fresh or processed into primary products, and the remainder is directly discarded. [2] This results in the underutilization of oyster meat and environmental pollution. Pearl oyster meat is rich in protein (74.9% on a dry basis) and contains unsaturated fatty acids, trace elements and vitamins, which may represent a valuable protein source for human nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Pearl oyster meat is rich in protein (74.9% on a dry basis) and contains unsaturated fatty acids, trace elements and vitamins, which may represent a valuable protein source for human nutrition. [2,3] Therefore, it is of great economic significance to develop a processing technology to turn this low-value byproduct into food sources.…”
Section: Introductionmentioning
confidence: 99%